Evaluation of antibacterial activity of cassia abbreviata oliv subsp abbreviata(caesalpiniaceae) abbreviata in diarrhoea against salmonella typhi and shigella flexneri in Zambia - Nachuma Clayton (Lusaka,the university of Zambia, school of medicine, 2016)
Resistance to drugs especially antibiotics has become a major challenge facing the medical frateenity today. Most antibiotics that were once effective against pathogenic micro-organismsmhave now been rendered inefgfective owing to resistance developed by these pathoges. These challenges call for renewed strategies on treatment, especially in development of new antimicrobials.
A report submitted in partial fulfilment of requirement of the university of Zambia for the award of bachelor of pharmacy degree.
Keywords: Antibiotics-Analysis; Drug resistance-Bacterial